2011 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2011
DOI: 10.1109/icassp.2011.5946499
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of human footsteps utilizing multi-axial seismic fusion

Abstract: This paper introduces a method of enhancing an unattended ground sensor (UGS) system's classification capability of humans via seismic signatures while subsequently discriminating these events from a range of other sources of seismic activity. Previous studies have been performed to consistently discriminate between human and animal signatures using cadence analysis. The studies performed herein will expand upon this methodology by improving both the success rate of such methods as well as the effective range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…A large number of experiments have shown that seismic waves are primarily composed of Rayleigh waves. Therefore, Rayleigh waves are widely used in seismic signal analysis [18]- [20].…”
Section: Mathematical Modeling a Formation And Propagation Princmentioning
confidence: 99%
“…A large number of experiments have shown that seismic waves are primarily composed of Rayleigh waves. Therefore, Rayleigh waves are widely used in seismic signal analysis [18]- [20].…”
Section: Mathematical Modeling a Formation And Propagation Princmentioning
confidence: 99%
“…In the domain of human sensing, seismic waves have been used to detect presence of humans [88,89], tracking and bearing estimation [90]. Mainly the seismic studies that consider animals have focused on differentiating between two categories (bipedal (human) and quadruped (animals) [78,91]). Few works on pure wildlife studies have focused on problems such as detection or classification of animals.…”
Section: Technologies For Eulerian Approachmentioning
confidence: 99%
“…Generally, this task can be achieved by systems of varying complexity, portability and cost, depending on the context in which they are deployed. A number of methods for footstep sensing have been proposed and developed since the 1980s, involving piezoelectric [1], [2], resistive [3], force [4], [5], capacitive [6], seismic [7] and acoustic sensing principles [8]. The utilized sensing technology has included load cells [9], [10], switches [11], electromechanical films [12], optical fibers [13], flatbed scanners [14], resistive loads [15] and accelerometers [16], as well as combinations thereof [17].…”
Section: Introductionmentioning
confidence: 99%